SHORT OVERVIEW OF ENCAPSULATION TECHNOLOGIES FOR DELIVERY OF BIOACTIVES TO FOOD - Trifković, K.; Tadić, G.; Bugarski, B. (Journal of Engineering & Processing Management, 2016)
Encapsulation strategy has emerged as a mean to protect sensitive bioactive compounds, to improve their stability and to deliver their active forms to the targeted place. A number of bioactives can be encapsulated – cells, enzymes, vitamins, minerals, aromas and flavours, food colourants, antioxidants, etc. Over the years various encapsulation technologies were employed in encapsulation of bioactive compounds intended to the application in food industry. This paper gives a short overview of commonly used technologies for the encapsulation of food bioactives.